Pemanfaatan Media Pembelajaran Berbasis Android Menggunakan Pendekatan Inkuiri Untuk Menguatkan Technological Pedagogical and Content Knowledge (TPACK) Calon Guru - Jakub Saddam Akbar; Djakaria Djakaria (Oxygenius: Journal Of Chemistry Education, 2023)
The purpose of this study is to find out the description of the use of Android-based learning media using an inquiry approach to strengthen technological pedagogical and content knowledge (TPACK) for preservice teachers. The type of research used in this research is library research using descriptive analysis. The data used comes from secondary data, namely scientific journals in the form of articles. The data collection method used is documentation with data analysis techniques in the form of content analysis. Based on the results of the review of the journals that have been carried out, the results show that the use of Android-based learning media using the inquiry approach can strengthen the Technological Pedagogical and Content Knowledge (TPACK) of preservice teachers because it can train, shape habbit and provide confidence for prospective teachers to master the content of the material to be taught as well as integrating pedagogy with the technology used.